Guests, Hosts, and Ghosts: Variations of Hostipitality (Hospitality/Hostility) on the Irish and the Continental Stage - P. Müller, Péter (FOCUS: Papers in English Literary and Cultural Studies, 2024)
Abstract: Languages harbor diverse memories within their vocabulary, often overlooked in tracing words back to their origins. Investigating these roots can unveil essential links between commonly used terms. For example, in Hungarian, "guest" (vendég) and "stranger" (idegen) share an etymological root, reflecting the inherent connection between guests and strangers. Similarly, English terms like "host" and "guest" derive from the same etymological source, as demonstrated by J. Hillis Miller. Jacques Derrida further explores the interplay between "hospitality" and "hostility," leading to the concept of "hostipitality," which encapsulates the inherent ambivalence in the guest/host relationship. This awareness underscores the constant flux between acceptance and rejection, reflecting the dynamic nature of human interaction. The dramatic potential of the guest/host relationship is evident throughout history, with the arrival of visitors serving as a frequent dramatic device. These arrivals often disrupt the lives of hosts, leading to imprisonment, betrayal, or other dramatic outcomes. Such examples highlight how guests can profoundly influence and even haunt the lives of their hosts, shaping dramatic narratives with their presence. The present article focuses on Irish plays in which the guest/host motif is central, as in J. M. Synge’s The Playboy of the Western World, Brian Friel’s Translations and The Communication Cord, Declan Hughes’ Halloween Night, and his new version of Molière’s Tartuffe, or Conor McPherson’s The Seafarer.